Effects of Different Particle-Sized Al Powders on Sintering Properties of Aluminum Paste in Crystalline Silicon Solar Cell - Peng Zhu; Yang Lu; Xiaolei Chen (International Journal of Photoenergy)
In this paper, the effects of particle size difference of aluminum (Al) powder on physical properties of Al powder and sintering properties of Al paste were investigated. For this purpose, respectively, Al powders with four mean particle sizes were used, which were obtained by two classifications using the same nitrogen atomization process. Thermal analysis results showed that the smaller the Al particle size, the lower the oxidation temperature and the higher the reaction enthalpy, indicating higher reactivity of the Al powder. Four Al powders were prepared into Al paste by the same process, and the resistances of the paste increased with the decrease of the particle size of the aluminum powder. Electrochemical capacitance-voltage profiler (ECV) and scanning electron microscope (SEM) analysis showed that the smaller the Al particle size, the thicker the back surface field (BSF) and the higher the doping concentration of BSF. It was found that the smaller size of Al powder limited the migration of silicon, which resulted in higher concentration of silicon (Si) in the Al-Si liquid phase. This leads to reaching a balance at a higher temperature between the recrystallization of silicon from the alloy liquid and the dissolution of silicon in the liquid alloy and a higher doping concentration and a higher effective BSF doping thickness. Results of the study will provide reference for further study and application of Al paste.